PERAN DAYA TARIK VISUAL MEDIA PEMBELAJARAN DIGITAL TERHADAP ANTUSIASME BELAJAR MATEMATIKA SISWA: STUDI LITERATUR - Aishka Fairana; Heni Pujiastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has changed the learning process, including mathematics learning, which is often considered difficult by students. This study aims to examine the effect of visual attractiveness in digital learning media on students’ enthusiasm for learning mathematics. The method used is a Systematic Literature Review (SLR) based on the PRISMA stages. The research data were obtained from 15 scientific articles published in the last ten years through Google Scholar and relevant national journal portals. Data analysis was conducted using content analysis techniques to identify patterns and findings from previous studies. The results show that visual elements such as colors, animations, learning videos, and interactive designs can increase students’ attention and engagement in mathematics learning. However, the effectiveness of learning media is also influenced by instructional design and student characteristics. Therefore, well-designed digital learning media can significantly improve students’ enthusiasm for learning mathematics.